The Effect of Kahoot As an Ice Breaker on EFL Students’ Motivation - Artati, Ni Luh Rahayu (STKIP AGAMA HINDU SINGARAJA, 2021)
Teachers are encouraged to increase students’ motivation by implementing innovative techniques and strategies. Ice breaker is one of teaching technique that can improve students’ learning motivation in which it provides a fun learning activity. The current study investigated the effect Kahoot as an ice breaker on EFL students’ motivation. This study was an experiment with posttest only control group design. The data were collected from a motivation questionnaire and analyzed using descriptive and inferential statistics. The results showed that students in experiment group shows higher level of motivation compared to students in control group. The result of t test showed that the mean difference between groups are significant. Thus, it can be concluded that Kahoot as an ice breaker effected EFL students’ motivation in learning.